Guideline for Development of Service Competencies of Low - cost Airline Ground Staffs: At Phuket International Airport - Noothong, Kittiphich; Monpanthong , Paithoon (Dusit Thani College Journal, 2020)
The objectives of this research were 1) to study the confidence of passengers affecting the service quality of ground receptionists in low cost airlines, 2) to evaluate the competencies for service capabilities of Low Cost Airline Ground Staffs, 3) to be a guideline for developing the capacity of Low Cost Airline Ground Staffs. The sample used in the research was 400 Thai passengers who received services from Low Cost Airline Ground Staffs at Phuket International Airport which was a quantitative research. The statistics used in data analysis were frequency, percentage, arithmetic mean, standard deviation, t-test statistics and One-Way ANOVA. The research results found that the confidence level in service competencies of Low-Cost Airline Ground Staffs was at high level. When separating two study results from service capability competencies of Low Cost Airline Ground Staffs such as Skills, Knowledge, and Attributes of each staff to work performance, the sample assessed that service capability competencies of Low Cost Airline Ground Staffs s were at high in knowledge and the confidence of passengers affected to the service quality of Low-cost Airline Ground Staffs by 5 SERVQUAL dimensions such as Reliability, Responsiveness, Assurance, Empathy, and Tangibility. When considering each aspect, the sample had the highest confidence in service quality in tangibility. The personal factors such as gender, age and income of the sample affected to the development guideline for service competencies of Low-Cost Airline Ground Staffs differently.